Developing Entrepreneurial Skills in Pharmacy Students - Laverty, Garry (Am J Pharm Educ, 2015)
Objective. To create, implement, and evaluate a workshop that teaches undergraduate pharmacy students about entrepreneurship. Design. Workshops with 3 hours of contact time and 2 hours of self-study time were developed for final-year students. Faculty members and students evaluated peer assessment, peer development, communication, critical evaluation, creative thinking, problem solving, and numeracy skills, as well as topic understanding. Student evaluation of the workshops was done primarily via a self-administered, 9-item questionnaire. Assessment. One hundred thirty-four students completed the workshops. The mean score was 50.9 out of 65. Scores ranged from 45.9 to 54.1. The questionnaire had a 100% response rate. Many students agreed that workshops about entrepreneurship were a useful teaching method and that key skills were fostered. Conclusion. Workshops effectively delivered course content about entrepreneurship and helped develop relevant skills. This work suggests students value instruction on entrepreneurship.